Feedforward based transient control in solid oxide fuel cells. (November 2016) - Madani, Omid; Das, Tuhin
Abstract: In SOFCs, transient control of fuel utilization is achievable via input-shaping. In this paper, the approach is generalized to a feedforward control problem for second-order LTI systems with two inputs and one output. One is a measurable, time-varying, exogenous input and the other is a control input. The problem studied is exact tracking of a constant reference using the plant's DC gain vector. The problem considers plant models that can be divided into known and unknown parts, and where feedback is unavailable. Although SOFCs have nonlinear dynamics, the linear abstraction nevertheless helps predict the observed effectiveness of input-shaping. Abstract : Highlights: Cancellation or attenuation of transients using feedforward based input-shaping. Shaping of control input using measured exogenous input and plant's DC gain vector. Derived conditions for effective feedforward under incomplete knowledge of plant. Approach generalized for LTI second order systems with two inputs and one output. Effective in attenuating transient fuel utilization in Solid Oxide Fuel Cells.